NEO6860, modality-selective TRPV1 antagonist: a randomized, controlled, proof-of-concept trial in patients with osteoarthritis knee pain. (November 2018) - Arsenault, Pierre; Chiche, Dan; Brown, William; Miller, Jeffrey; Treister, Roi; Leff, Richard; Walker, Philippe; Katz, Nathaniel
Abstract: Introduction: NEO6860 is a TRPV1 antagonist when activated by capsaicin but not by heat or pH, developed to relieve pain without the adverse events reported with non–modality-selective TRPV1 antagonists. Objective: The primary Objective of this study was to evaluate the analgesic efficacy and safety of NEO6860 after 1 day oral dosing in patients with Kellgren-Lawrence stage I, II or III osteoarthritis of the knee. Method: This randomized, double-blinded, 3-period crossover, phase II study compared 1 day (2 doses) of NEO6860 (500 mg twice a day), placebo, and naproxen in 54 patients with osteoarthritis knee pain. Primary endpoint was reduction in pain intensity (PI) on Numerical Rating Scale after exercise, using the staircase test, 8 hours after dose. Results: Level of PI, compared with baseline, was numerically lower during NEO6860 and naproxen periods vs placebo at 3 and 24 hours, but not at 8 hours after first dose. A statistically significant effect for naproxen and a trend for NEO6860 were observed at 3 and 24 hours. Least square means' (95% confidence interval) change in PI at 24 hours was −0.67 (−1.09 to −0.26), −0.97 (−1.39 to −0.55), −0.29 (−0.71 to 0.13) for NEO6860, naproxen, and placebo, respectively. NEO6860 exposure was ∼1.6 times higher compared with previous phase I. In this study, NEO6860 safety profile was less favorable than naproxen or placebo. Possibly NEO6860-related adverse events included: feel hot, headache, nausea, dizziness, fatigue, hypoaesthesia, and increased blood pressure. Conclusion: In this exploratory study, NEO6860 did not statistically significantly outperform placebo but showed an analgesic trend, without impacting body temperature and heat pain perception. Further studies are warranted to explore the potential of NEO6860 in other pain indications. We intent to optimize the dose and evaluate analgesic synergism with other mechanism.